Heart failure re-hospitalization differently affects the following mortality in patients with reduced, mid-range and preserved LVEF. (14th October 2021) - Abe, T; Jujo, K; Watanabe, S; Kishihara, M; Shirotani, S; Takada, T; Yoshida, A; Saito, K; Hagiwara, N
Abstract: Introduction: The recent advances in the treatment for heart failure with reduced ejection fraction (HFrEF) have been remarkable, while no therapy has convincingly improved the prognosis in HF patients with preserved (HFpEF) and mid-range (HFmrEF) ejection fraction. Frequent decompensations of HF lead to progressive deterioration of cardiac and renal function, and quality of life. Hence, prior studies have reported that the mortality of HFrEF patients increases as hospitalization for HF repeats. However, it is still unclear whether this trend applies for HFpEF and HFmrEF patients. Purpose: We aimed to compare the prognostic impact of re-hospitalization due to HF on cardiovascular death (CVD) among HFrEF, HFmrEF and HFpEF patients. Methods: This observational study included 1, 930 consecutive patients who were hospitalized for worsening of HF and discharged alive. Of them, patients who have never or have not been hospitalized for HF at least last 2 years, were finally analyzed. Patients were consisted of the population with HFrEF (EF<40%, n=421), HFmrEF (EF 40–49%, n=202) and HFpEF (EF>50%, n=291). Patients in each EF-classified population were divide into 2 subgroups based on whether patients were re-hospitalized for HF during the observational period, respectively. The primary endpoint of this study was CVD. Results: During the observation period, Kaplan-Meier analysis showed that patients who were re-hospitalized for HF had higher event rate of CVD in HFrEF group (Log-rank p=0.008, Figure). Even after adjusting with multivariate covariates including age, sex, EF, brain natriuretic peptide and estimated glomerular filtration rate, re-hospitalization for HF was an independent predictor for CVD in HFrEF group (HR: 1.95, 95% CI: 1.11–2.86, p=0.029). However, in HFmrEF group and HFpEF group, there was no significant difference in the rates of CVD between 2 subgroups divided whether patients were re-hospitalized for HF or not (p=0.91, p=0.34, respectively). Conclusion: Re-hospitalization for HF affected the CVD rate in HFrEF group, but not in HFmrEF and HFpEF groups. The prevention of re-hospitalization for HF is important particularly in HFrEF patients in order to improve cardiovascular mortality. Funding Acknowledgement: Type of funding sources: None.